Elemental and Molecular Composition of Humic Acids Isolated from Soils of Tallgrass Temperate Rainforests (Chernevaya taiga) by 1H-13C HECTCOR NMR Spectroscopy - Vyacheslav Polyakov; Sergey Loiko; Georgiy Istigechev; Alla Lapidus; Evgeny Abakumov (Agronomy, 2021)
The soils of Chernevaya taiga (tallgrass fir-aspen hemiboreal rainforest) have high fertility in comparison with oligotrophic analogs formed in boreal taiga. We have studied humic acids isolated from the soils of Chernevaya and oligotrophic taiga in the Novosibirsk, Tomsk, Kemerovo and the Altai regions of Russia and for the first time the structural and molecular composition of humic acids was determined using 13C CP/MAS and 1H-13C HETCOR NMR spectroscopy. According to data obtained in this study, up to 48% of aromatic compounds accumulate in the soils of Chernevaya taiga, which is higher than in the oligotrophic taiga and comparable with this rate of steppe Chernozems. In the course of active processes of transformation of organic matter, a significant number of aromatic fragments accumulates in the middle horizons of soil profiles. Using 13C CP/MAS spectroscopy, it was possible to identify the main structural fragments (aliphatic and aromatic) that formed in humic acids of the Chernevaya taiga. The HETCOR experiment made it possible to accurately determine the boundaries of chemical shifts of the main groups of structural fragments of humic acids. Our results demonstrate that the stabilization of organic compounds occurs in the soil of the Chernevaya taiga, which leads to the resistance of organic matter to biodegradation that is not typical for benchmark soils of boreal environments.